Biophysical and in silico characterization of the interaction of anticancer drugs with human serum albumin / Salanee Kandandapani - Salanee , Kandandapani (2022)
Tyrphostin 9 (Tyr 9), pazopanib (PZP) and regorafenib (REG) are potent platelet-derived growth factor receptor (PDGFR) inhibitors, and induce apoptosis in various cancer cell types such as chronic myeloid leukemia, soft tissue sarcoma, renal cancer, colorectal cancer and gastrointestinal stromal tumors. The binding of these drugs to the major transport protein in human circulation, human serum albumin (HSA) was investigated using fluorescence and UV-vis absorption spectroscopic techniques as well as molecular docking methods. Fluorescence quenching titration results showed progressive decline in the protein fluorescence with increasing drug concentrations. A decreasing trend of the Stern-Volmer constant, Ksv with increasing temperature characterized the drug-induced quenching as static quenching, thus pointed towards the formation of Tyr 9/PZP/REG–HSA complexes. This was further confirmed by the hyperchromic effect seen in the UV-vis absorption spectra of HSA upon addition of these drugs. The binding constant (Ka) values of these drug–HSA systems were found to lie within the range 1.29–3.56 × 105 M-1 at 298 K, which suggested moderate binding affinity between these ligands and HSA. The drug–HSA complexes were found to be stabilized by hydrophobic interactions, van der Walls forces and hydrogen bonds, based on the thermodynamic data [(ΔS° = + 13.90 J mol–1 K–1 and ΔH° = – 26.60 kJ mol–1for Tyr 9– HSA system); (ΔS° = + 98.37 J mol–1 K–1 and ΔH° = – 60.31 kJ mol–1for PZP–HSA system); (ΔS° = + 17.17 J mol–1 K–1 and ΔH° = – 23.00 kJ mol–1for REG–HSA system)]. These results were further supported by the molecular docking analyses. Interaction of Tyr 9, PZP and REG with HSA also produced microenvironmental perturbations around protein fluorophores (Tyr and Trp), as evident from the 3-D fluorescence spectral results but increased protein’s conformational stability against thermal denaturation. Competitive drug displacement results along with molecular docking analyses suggested Sudlow’s Site I of HSA as the preferred Tyr 9, PZP and REG binding site.